Approaches to avoid flooding in association with pressure drop in proton exchange membrane fuel cells. (15th August 2018) - Li, Yuehua; Pei, Pucheng; Wu, Ziyao; Ren, Peng; Jia, Xiaoning; Chen, Dongfang; Huang, Shangwei
Highlights: Water management based on cathodic pressure drop is conducted. Varying fuel cell temperature, inlet pressure, RH are used to do this management. Flooding can be avoided using these methods. Impedance lowers during regulation and increases again if not regulated. Varying inlet pressure is a most effective way coupled with pressure drop. Abstract: The cathodic pressure drop (PD) of proton exchange membrane fuel cell (PEMFC) can be used to conduct water management as it can perceive the water amount interior the fuel cell. Our previous research proposed the strategy to conduct this kind of management. In this paper the specific approaches, including regulating fuel cell temperature, inlet pressure, and inlet relative humidity (RH), were adopted to fulfill this strategy. The regulation was executed in case the real PD surpasses the theoretical control line. The electrochemical impedance spectroscopy (EIS) was tested to present the water amount. During more than three hours' operation, the flooding did not occur anymore using the three management approaches. Of them, increasing the inlet pressure 25 kPa enabled voltage to recover 25 mV and made the performance not decline obviously. As a contrast, an 8 mV recovery was achieved via increasing temperature 2 K. The recovery range got much less if regulated inlet RH. In commercial fuel cell system, changing inlet pressure in a normal regulation range is a promising way to avoid flooding. This comprehensive approach based on PD can be directly used in the fuel cell system via sending commands to air compressor and air back pressure valve, without deploying extra devices.